“Bad Things”. L’érotique solaire à la Tenor - Nankeu, Bernard Bienvenu (Ponti/Ponts, 2021)
Eroticism is a sexual modality, which beyond the act in its physical essence in question, engages partners in a mutualisation of the act, a total and entire admiration of the body of the other, a way to pour out favoring sharing, mutual satisfaction and a certain elevation above the common place of the relationship. The article is an erographic reading of erotic figures and postures from the song “Bad Things” by the Cameroonian artist Tenor. In this tube and through a melee moment where slowness, coaxing, sacredness, joint obligation, immoderation and paradoxically discipline are in order, sexuality is lived and thought in an integral, spiritual way, mystical and transcendental. This gives to see a more erotic-relational aspect of the Cameroonian sexual mores on the one hand and African on the other hand, but very often ignored, especially at this time when sex is in tune with the times, by racist stereotypes which make of the Black a genital, luxurious, wild being and the moralistic interpretations which, without distinction, include everything under the label of provocative pornography.